Floral stimulation in prickly pear cactus in response to the effect of Thidiazuron - Víctor Gómez, Emmanuel; López-Jiménez, Alfredo; Cortes-Flores, José I.; Jaén-Contreras, David; Suárez-Espinoza, Javier (Revista Mexicana de Ciencias Agrícolas, 2020)
On average, the yield of prickly pear (Opuntia ficus-indica) is low, being 5.5 t ha-1 / year. The nopal tuner cladodes have only sprouting in the periphery, representing 30% of total buds / cladode, wasting the lateral spaces of the penca. Using biostimulant in conjunction with plastic cover and irrigation to increase floral budding and yield is the objective of this research. Prickly pear cactus plants ‘Red purpura’ 4 years old, with a planting distance of 3x4 m. There were two factors: 1) Dose of TDZ: 0 ppm, 400 ppm, 800 ppm. 2) Joint plastic cover with irrigation: without cover and without irrigation, without cover and with irrigation, with irrigation and without cover, with irrigation and with cover; in 3x4 factorial arrangement, with 12 treatments and three repetitions in divided plots. The experimental unit was a group of four cladodes. 44 days after applying TDZ, the treatment 800 ppm of TDZ, obtained a higher percentage of flower buds with 53.9%, followed by irrigation cover with 400 ppm of TDZ with 46.8%, exceeding 12.7% of the control. Twenty-two days after the application of TDZ, the plants with plastic cover began to reverse floral and vegetative buds, this phenomenon and the appearance of new shoots, both vegetative and floral, stopped 44 days after applying TDZ, it is suggested that the cover, raised and maintained the temperature to stimulate vegetative sprouting and cause floral reversal.